Pengaruh Leverage, Ukuran Perusahaan, dan Nilai Perusahaan Terhadap Cash Holding - Nurwani Nurwani (CERED Indonesia Institute, 2021)
Cash is a liquid part of current assets to be used in improving company performance, especially earning profits and paying corporate liabilities. The purpose of this research was to examine the influence leverage, firm size, and firm value on cash holding partially and simultaneously. The population of this research was plastics and packaging subsector manufacture companies listed in the Indonesia Stock Exchange in the period of 2014- 2019. The sample of research amount to 5 companies selected by using purposive sampling technique. The data were processed by using multiple linear regression analysis. The result of the research showed that leverage and firm value had influence significant on cash holding partially, while firm size had no influence significant on cash holding partially. Finally, leverage, firm size, and firm value had influence significant on cash holding simultaneously. Keywords : Leverage, Firm Size, Firm Value, Cash Holding